Priority Assignment Algorithms for Maximum Protection Ratio in Shared Mesh Protection - Lalaji, Krishnendu; Eapen, Remya Annie (2021 International Conference on Computer Communication and Informatics (ICCCI), 2021)
Shared mesh protection is a fault recovery mechanism that is used for the fast recovery of traffic when a network failure occurs. Protection paths having different endpoints share their resources leading to the contention of services when multiple failures occur. Preemption is to be done when many services contest for the same resources. The optimization problem is to maximize the total protected services for any failure case. To find the optimal priority set, algorithms such as depth-based algorithm, minimum degree algorithm and capacity density algorithm are used. In this paper, we propose Hungarian capacity density algorithm to find the optimal priority set. The performance of all the algorithms are compared with respect to the protection ratio.